FIKIH GOOD GOVERNANCE (Electronic Government dalam Nalar Mashlahat) - Helim, Abdul (LP2M IAIN Palangka Raya, 2009)
The main motivation of this article is to explore the trend of modern people in using of technology development in some sectors especially in government bureaucracy. The purpose ofÂ this article is to discuss the existence and e-government law status in logical benefit. Normative study in Islamic law is done by the primary, secondary, tertiary case that can be displayed through the inductive and deductive method used by contextual approach model. Analysis data were done by the content analysis that was supported by adaptional-participational theory. E-government is a contemporer problem that can be seen in the study of laws pertaining to ritual obligations. The present of e-government is to increase the efectiveness to work in giving the best service to Indonesian people. There are some advantages that can be gotten and proved empirically by the implementation of e-government. The problems were limited the number of qualified human resources and infrastructure to support of the e-government. The governmentâ attention to the implementation of e-gov is very important. Therefore, significantly, e-gov is as the information publication medium, interaction, and transaction forum. These advantages could be primary, logically, and it was not in contradiction to the Islamic law. At the present, e-gov should be applied in the real life. Meanwhile, if the process and outcome of the implementation of e-gov can be found some distortion, so e-gov is a activity that is forbidden to be done.Â